The language style of the main javanese female character in the Kartini film by Hanung Bramantyo - Olivia Andi Calista; Udjang Pairin M.Basir (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
Communication between humans is the primary function of language. Language is an arbitrary system of symbols of sound that is used by members of social groups to cooperate, communicate, and identify themselves. It can be interpreted asa study of language in relation to society or how it functions in society. Sociolinguistics experts say that speakers involved ina speech event must have a communicative competence or knowledge of language systems combined with existing rules or norms in society in order to make proper use of language ina speech situation. Therefore,people in the community adjust to their environment there are speaking and speaking styles in the community. The results of this research are controlled by codes and interlaced codes. Temporary override codes to produce data using indonesian-java, Java ngoko-java kromo. To override the permanent code, produce a file of Javanese use of good manners for people who respect such nobility. The result of the code-mixing only exists a positive mixing because this film is free of Sara's sentences. The study's code combines both Indonesian and Javanese (ngoko and krama) in one clause.